Horizontal and vertical optic disc rotation. The Beijing Eye Study - Fan, Yuan Yuan; Jonas, Jost B. (PLOS ONE, 2017)
To measure the optic disc rotation around the vertical and horizontal disc axis and to evaluate associations with general and ocular parameters.